(untitled) (International Journal of Information and Electronics Engineering, 2024)
Nowadays, image processing applications are frequently preferred in such fields as industrial automation, security, health, and traffic control in parallel with the developments in technology. The most important criterion for the applications used in these fields is to ensure the system to run at high speed and real time. Thus, FPGAs are commonly used in such applications. In this study, some of the basic real time images processing algorithms are implemented in a FPGA-based development kit. The ZedBoard Znyq-7000 development kit produced by Xilinx Company was used in the study. As a result of grayscale conversion and convolution operations, such applications as edge detection, sharpening and blurring were realized on the images taken by video source. The processed images were viewed by the use of a monitor connected to HDMI output of the development kit. Verilog HDL was used for these operations.